PELATIHAN DAN PENGEMBANGAN DALAM MENINGKATKAN PROFESIONALITAS TENAGA PENDIDIK DI MTs ANDALUSIA BANJARNEGARA - Maftukhul Ngaqli; Ahsin Wijaya; Nurul Mubin (Pendidikan Agama Islam (S2), UNSIQ Wonosobo, Jawa Tengah, 2021)
Against the background of the importance of the figure of educators for the success of learning and realizing the goals of national education, the empowerment of human resources, especially educators, is fundamental. One of the efforts to improve the quality or competence of educators is through training and development programs for educators. This type of research uses descriptive qualitative with the research approach used is: phenomenology. The data sources of this research are the Head of Madrasah and Educators. Furthermore, the data collection methods used were observation, interviews and documentation. Then the data processing and analysis techniques were carried out through three stages, namely: data reduction, data presentation, and drawing conclusions. The results showed that: (1) The training and development program for educators at MTs Andalusia Banjarnegara included: upgrading skills, microteaching, article writing, MGMP, webinars, further education and book study activities. (2) The process of implementing the training for educators at MTs Andalusia has been regularly scheduled, it's just that internal training is still limited to a less intense time and external training is limited to confirmation of invitations and waiting for the appointment of the madrasa head. Meanwhile, the education staff development program is still not optimal in terms of program support and needs analysis. (3) The impact of training and development of educators in improving the professionalism of educators are: Improving information technology skills and modernizing educators; Improve classroom management and public speaking skills; Improve literacy skills and analysis learning; Improve the optimization of mastery of learning materials; Increase knowledge of global insight and networking; Career advancement; Personality enhancement is commendable.